2018
DOI: 10.1111/jphp.13055
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, chemical characterization and determination of crocetin's pharmacokinetics after oral and intravenous administration of saffron (Crocus sativus L.) aqueous extract to C57/BL6J mice

Abstract: Objectives To prepare a lyophilized saffron aqueous extract (SFE) and determine its chemical profile and serum and tissue pharmacokinetics after intravenous and oral administration to C57/Bl6J mice. Methods Lyophilized SFE was prepared, characterized using semi‐preparative HPLC and NMR analysis, and stability studies at room temperature, and was quantified for crocin content with an HPLC‐PDA method. After intravenous and oral administration of SFE (60 mg/kg, reconstituted with water for injection) to C57/Bl6J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
(69 reference statements)
0
25
1
3
Order By: Relevance
“…Some pharmacokinetic studies on CS reported that the intestinal deglycosylation of various crocins is primarily due to the enzymatic processes in the epithelial cells. In these reports, minor crocins may be deglycosylated by the fecal microbiome, facilitating transformation into TCT finally [36,37]. The values of C max and AUC 0−t of TCT in the present study were much higher than other crocins.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Some pharmacokinetic studies on CS reported that the intestinal deglycosylation of various crocins is primarily due to the enzymatic processes in the epithelial cells. In these reports, minor crocins may be deglycosylated by the fecal microbiome, facilitating transformation into TCT finally [36,37]. The values of C max and AUC 0−t of TCT in the present study were much higher than other crocins.…”
Section: Discussioncontrasting
confidence: 49%
“…The data for bioanalytical studies showed that HPLC-based quantification had been reported for the presence of trans-4-GG-crocin (T4C) or crocin-1 and trans-crocetin (TCT) in CS [4,[35][36][37]. But there is no report of the methodology for bioactive apocarotenoids PIC and SAF along with other carotenoids trans-3-Gg-crocin (T3C), trans-2-gg-crocin (T2C), cis-4-GG-crocin (C4C) from CS [35][36][37]. This research also lacks confirmation and detection of these compounds in biological samples after CS or its extract or product consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Crocetin levels in blood were higher after oral administration than in intravenous administration, probably due to the wide hydrolysis of the crocins in the intestinal lumen to trans -crocetin, which is rapidly absorbed by passing blood through the portal vein. The analysis of the tissues reveals an extensive distribution of crocetin in the liver and kidneys [108]. The advances in the knowledge of the bioaccesibility of bioactive compounds of saffron will contribute to developing their biomedical applications.…”
Section: Bioactivity Of Crocus Sativus L Compoundsmentioning
confidence: 99%
“…54,57,58 According to a recent study in 2019, fast intestinal absorption of saffron extracts leads to a higher serum level of crocetin compared with intravenous administration. 59 The active components of saffron have been shown to possess antidepressant and antitumor effects, while they are able to neutralize free radicals and reduce inflammation. 20,21 Taken together, saffron might be a candidate for research on neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%